Impacts of stall and structural nonlinearities on the stability of aeroelastic - Bouma, A.; Yossri, W.; Vasconcellos, R. [UNESP]; Abdelkefi, A.; AIAA (Amer Inst Aeronautics & Astronautics, 2021)
The effects of stall, quadratic, and cubic nonlinearities in the pitch degree of freedom on the behavior of a two-degree of freedom aeroelastic system are investigated. The nonlinear governing equations of the considered aeroelastic model are derived and discussed along with modeling of the aerodynamic loads based on two different approximations and results and conclusions are presented. Comparisons between quasi-steady and unsteady aerodynamic representations are investigated and discussed including stall effects. The unsteady representation based on the Sears and Pade approximations is used to model the aerodynamic loads. The nonlinear aeroelastic response is carried out in the presence of structural nonlinearities before and after the onset of flutter. The effects of the stall and unsteadiness of flow on the Hopf bifurcation are investigated along with a stability analysis of the two-degree of freedom system depending on the nonlinearities present and the stall effect. Results show that the choice of the aerodynamic representation can be critical on the prediction of the stability in the flutter boundary region and the pre- and post-flutter responses of the system.